Penerapan PMT Berbasis Bahan Herbal dalam Meningkatkan Pengetahuan Kader Posyandu Stunting di Desa Lemahbang Pasrepan Pasuruan - Khoirin Maghfiroh; Cahyaning Rini Utami; Romadhiyana Kisno Saputri (Universitas Nurul Jadid, 2024)
This study aims to evaluate the effectiveness of implementing a herbal-based Supplementary Feeding Program (Pemberian Makanan Tambahan or PMT) in enhancing the knowledge of Posyandu Stunting (POSTING) cadres in Lemahbang Village, Pasrepan, Pasuruan. The method used is Participatory Rural Appraisal (PRA), encompassing observation, focus group discussions (FGDs), training on PMT product development, technology application assistance, healthcare services, and outcome evaluation. The partners in this study were all POSTING cadres in Lemahbang Village. The PMT products created included temulawak (Curcuma xanthorrhiza) milk drinks and kelor (Moringa) seaweed snacks.The results of this Community Service Program (PKM) showed significant improvements in knowledge, skills, interest, and PMT product quality, as measured through questionnaires and interviews conducted before and after the program. Findings indicate a substantial increase, with a 50-80% improvement in POSTING cadres' understanding of nutrition, the benefits of herbal ingredients, and PMT product development. The resulting PMT products were more nutritious and had an extended shelf life.